2008
DOI: 10.1007/s11104-008-9593-5
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum distribution and reactive oxygen species accumulation in root tips of two Melaleuca trees differing in aluminum resistance

Abstract: To elucidate the mechanism of the high aluminum (Al) resistance of a Myrtaceae tree, Melaleuca cajuputi Powell, we investigated the responses of root tips to Al and compared them with those of an Al-sensitive species, M. bracteata F. Muell. Roots of seedlings of both species were treated with a calcium solution (pH 4.0) containing 0 or 1 mM AlCl 3 . After 3 h of Al treatment, inhibition of root elongation and deposition of callose and lignin in root tips, typical signs of Al injury, were induced in M. bracteat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 55 publications
0
30
0
1
Order By: Relevance
“…Mg ion might be an important component of characterizing the physiology of Al resistance. Al 3+ toxicity may also provoke similar mitochondrial dysfunction [71] and ROS production in many plant species [72][73][74][75][76] presumably by causing Mg deficiency inside the mitochondria or by substituting Mg for Al 3+ in Mg 2+ -dependent enzymes [77,78]. Thus, mitochondrial Mg porters could be the target site for Al 3+ toxicity.…”
Section: Mitochondriamentioning
confidence: 99%
“…Mg ion might be an important component of characterizing the physiology of Al resistance. Al 3+ toxicity may also provoke similar mitochondrial dysfunction [71] and ROS production in many plant species [72][73][74][75][76] presumably by causing Mg deficiency inside the mitochondria or by substituting Mg for Al 3+ in Mg 2+ -dependent enzymes [77,78]. Thus, mitochondrial Mg porters could be the target site for Al 3+ toxicity.…”
Section: Mitochondriamentioning
confidence: 99%
“…To determine whether the presence of oenothein B is ubiquitous in plants, we analyzed root extracts of three Al-sensitive species: Melaleuca bracteata (Myrtaceae; Tahara et al, 2008b), Populus nigra (Schaedle et al, 1989), and Arabidopsis (Fig. 4).…”
Section: The Relationship Between Oenothein B Content and Al Resistancementioning
confidence: 99%
“…Al-induced generation of ROS has been shown in maize (Zea mays) and Allium cepa roots (Jones et al, 2006;Achary et al, 2008). Tahara et al (2008) showed that ROS generated to a greater degree in Alsensitive species than in Al-tolerant species. Yamamoto et al (2002Yamamoto et al ( , 2003 have shown a correlation between ROS level and inhibition of growth capacity in cultured tobacco (Nicotiana tabacum) cells.…”
mentioning
confidence: 99%